Analysis of Students' Difficulties In Solving Minimum Competency Assessment Questions In Terms of Mathematical Communication Skills - AL-Ashri, Lazuardi Sastra; Awalludin, Subhan AJiz (Universitas Wiralodra, 2023)
The minimum competency assessment is used in developing students' numeracy literacy skills to have 21st-century skills. However, students' difficulties in solving minimum competency assessment questions will cause unsatisfactory results. Therefore, it is necessary to analyze further students' difficulties in solving the minimum competency assessment questions, including mathematical communication skills. This study used qualitative research methods with descriptive analysis techniques to examine these difficulties. The data collection techniques used were observation, tests, and interviews. The research was conducted by giving students a minimum competency assessment test, and then the results were analyzed so that six research subjects were obtained. Then interviews were performed according to the guidelines that had been made for the six subjects. The results showed that subjects with high communication skill categories needed help compiling solution ideas and complete answers written by students. Then subjects in the medium category had difficulty in three indicators: linking the information given into mathematical concepts, compiling mathematical ideas, and generalizing. Meanwhile, subjects in the low category experienced difficulties in each indicator, and most did not answer the questions. So it is concluded that subjects with high communication ability categories have fewer difficulties when solving minimum competency assessment questions than subjects with medium and low levels.